EXPLORING EFFECTIVE STRATEGIES TO IMPROVE STUDENT DISCIPLINE POST-PANDEMIC AT SCHOOL AND AT HOME - Rolina Saragih; Dylmoon Hidayat (PROGRES PENDIDIKAN, 2026)
Discipline is a prerequisite for creating a conducive educational environment for teaching and learning. The implementation of discipline in schools aims to achieve learning objectives aligned with the school's vision and mission and to achieve national education goals. Following the COVID-19 pandemic, students have experienced a decline in character values such as good manners, discipline, and responsibility, as evidenced by numerous violations at school. This article discusses factors influencing student discipline, the role of parents and teachers in improving student discipline, and effective strategies that teachers and parents can implement to improve student discipline post-pandemic. The method used to write this article is a literature review and a qualitative discussion of the results. The author's findings indicate that factors influencing student discipline are students themselves and their environment, including teachers and parents. Teachers and parents are expected to work together diligently to implement the same strategies at home and at school: explaining rules and their consequences, modeling, habituation, supervision, and control. In implementing these strategies, teachers and parents can provide stimuli for students, namely rewards and consequences appropriate to the student's age. It is hoped that teachers and parents will continue to innovate in implementing the strategies presented so that efforts to improve student discipline post-pandemic will yield satisfactory results.